Role of Metal Ions, Surfactants and Solvents on Enzymatic Activity of Partial Purified Glucoamylase from Aspergillus niger ER05 - Erum Hanif,; Shah Ali Ul Qader ,; Raheela Rahmat Zohra, (Journal of Basic & Applied Sciences, 2018)
The glucoamylase requirement of different industries should vary in their physiochemical and functional properties, so the investigation of new sources for the novel enzymes is the only solution. The current study describe the production of glucoamylase from Aspergillus niger ER05 in a submerged fermentation. The enzyme then partially purified and then effect of thirteen different metal ions (Cs+, K+, Na+, Ba2+, Ca2+ Co2+, Cu2+ , Hg2+, Mg2+, Mn2+, Ni2+, Zn2+ , Fe3+), surfactant as well as organic solvent on catalytic performance of glucoamylase was studied. A newly isolated Aspergillus niger ER05 is hyper producing strain of glucoamylase. Specific activity for the crude enzyme was found to be 6.87 KU/mg. The crude enzyme was partially purified via fractional ammonium sulphate precipitation. Ammonium sulphate saturation from 40-80% was found suitable to precipitate the enzyme. After dialyzing precipitates, the specific activities were found to be 66.33KU/mg with percent yield of 26.5. The inhibitory influence of all metal studies was interestingly found on glucoamylase activity. The strong inhibition was demonstrated in presence of Hg2+, Ni2+, Zn2+, Cu2+, Fe3+. Only Na+ ions were able to maintain the 101% relative activity at 1mM concentration. The SDS completely inhibits the enzyme activity and in presence of tween-80 and triton X-100 glucoamylase exhibited less than 45% relative activity. Furthermore, formaldehyde, isopropanol, ethanol, methanol, and DMSO stabilized the enzyme activity while chloroform inhibits enzyme activity by 48%.